2016
DOI: 10.4103/0019-5049.187783
|View full text |Cite
|
Sign up to set email alerts
|

An observational cohort study on pre-operative investigations and referrals: How far are we following recommendations?

Abstract: Background and Aims:Pre-operative investigations are often required to supplement information for risk stratification and assessing reserve for undergoing surgery. Although there are evidence-based recommendations for which investigations should be done, clinical practice varies. The present study aimed to assess the pre-operative investigations and referral practices and compare it with the standard guidelines.Methods:The present observational study was carried out during 2014–appen2015 in a teaching institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…[ 5 ] This leads to many unnecessary or unindicated tests and a huge cost burden. [ 6 7 ] The present study also found similar results. More than 60% of anaesthesiologist and more than 70% of surgeons believe that pre-operative tests will detect a hidden abnormality.…”
Section: Discussionsupporting
confidence: 89%
“…[ 5 ] This leads to many unnecessary or unindicated tests and a huge cost burden. [ 6 7 ] The present study also found similar results. More than 60% of anaesthesiologist and more than 70% of surgeons believe that pre-operative tests will detect a hidden abnormality.…”
Section: Discussionsupporting
confidence: 89%
“…The practice of ‘routine’ investigation has been questioned by several studies. [345] Prevalence of abnormal results in routine preoperative tests is around 5-60% although it may vary with the American Society of Anesthesiologists Physical status of patients. [56789] Studies that have focused on ASA 1 and 2 patients, report very low prevalence (0.8%) of abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus of these guidelines is that unnecessary tests may lead to extra cost burden, delay in surgery and occasional harm to the patient. [34] It is possible that these guidelines may not entirely be applicable to the Indian population. The present study was aimed to compare the preoperative laboratory investigations ordered in a referral medical college hospital of South India with the National Institute of Clinical Excellence (NICE) guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] However, the practice of routine pre-operative tests before elective surgery has remained widely prevalent. [ 4 5 ] Health-care practices not only depend on practitioners' knowledge but also on the local laws, protocols, administrative policies, etc. The present study was aimed to assess the reasons behind this continued practice.…”
Section: Introductionmentioning
confidence: 99%